IMPROVING CITIZENS LEARNING OUTCOMES IN DIVERSITY MATERIALS THROUGH EXAMPLES NON EXAMPLES LEARNING METHODS - Masadiah, Masadiah (Universitas Tanjungpura, 2021)
AbstractOne of the problems in the world of education today is the low quality of education caused by several factors including the low quality of learning caused by the ability of teachers who are still lacking, not using methods that are in accordance with the material being taught, an evaluation system that is not appropriate, and the ability of teachers. The purpose of this Classroom Action Research (CAR) is to determine the extent to which learning through examples non-examples learning methods can improve the learning outcomes of grade VII A students at SMP Negeri 5 Sungai Raya. This research was carried out in 2 cycles. The Learning Methods Examples Non Examples technique is proven to be able to improve students' poetry writing skills in Indonesian lessons by reaching the KKM standard of 70. From 64.62% in cycle I, it can increase to 78.70% in cycle 2. The results of this action research indicates that the examples non examples learning method is useful and can improve students’ learning outcomes in Civics subjects in class VII A at SMP Negeri 5 Sungai Raya. Keywords: Learning Methods Examples Non Examples, Learning Outcomes